Laboratory study on the deformation resistance indicators of asphalt mixture based on the rutting deformation growth model - Lihua Liu; Zhaoyu Sun (PLoS ONE, 2026)
Rutting tests were conducted to investigate the deformation resistance of asphalt mixtures under varying temperature and wheel load conditions. The significant effect of temperature and load on the deformation resistance of the asphalt mixture was investigated using ANOVA. Multiple deformation resistance indicators, including complex stability index ( CSI ), densification coefficient (D), shear index(1/ E ), and characteristic parameters ( A , C , and A/C ), were proposed based on the rutting deformation growth equation, and the correlation model between rutting deformation and each indicator was established. The validity and reliability of the deformation resistance indicators were verified and evaluated. The results demonstrated that both the dynamic stability and rutting deformation of the asphalt mixture are more sensitive to temperature than load at the 0.05 significance level. The correlation between the proposed indicators and rutting deformation were significantly stronger than that between dynamic stability and rutting deformation. Additionally, indicators A and A / C exhibit high level of correlation when predicting permanent rutting deformation. The proposed deformation resistance indicators can accurately predict the permanent rutting deformation in laboratory rutting tests, which can provide reference for studying long-time rutting deformation in laboratory rutting tests.